Analyses of free amino acid and taste sensor traits in egg albumen and yolk revealed potential of value‐added eggs in chickens. (8th January 2021) - Goto, Tatsuhiko; Shimamoto, Saki; Ohtsuka, Akira; Ijiri, Daichi
Abstract: To create high‐quality eggs by using different breed and feed materials, we investigated free amino acid contents and taste sensor traits using two chicken breeds (Rhode Island Red; RIR and Australorp; AUS) fed two feeds (mixed and fermented feeds). Two‐way ANOVA revealed significant breed and feed main and interaction effects on albumen bitterness and a significant interaction effect on yolk bitterness. Albumen from RIR fed mixed feed and AUS fed fermented feed was higher bitterness, whereas yolk from those groups was lower bitterness. Significant breed effects were detected in four albumen amino acid traits (His, Met, Ile, and Lys) and a yolk His, whereas significant feed effects were found in 15 albumen amino acid traits (Asp, Glu, Ser, His, Gly, Thr, Ala, Tyr, Val, Met, Trp, Ile, Leu, Lys, and Pro) and a yolk cystine trait. Compared to albumen amino acids, yolk amino acids had limited effects by breed and feed. The present results suggest that genetic and nutritional factors can alter not only amino acid contents but also sensor values of bitterness, indicating that selecting the combination of breed and feed enable us to make amino acids enriched and taste added designer eggs in future.